KAJIAN YURIDIS KEPEMILIKAN RUMAH/HUNIAN DAN BANGUNAN OLEH ORANG ASING BERDASARKAN PERATURAN MENTERI AGRARIA DAN TATA RUANG/KEPALA BADAN PERTANAHAN NASIONAL NOMOR 29 TAHUN 2016 - KITA SATELITA PINEM (PREMISE LAW JURNAL, 2017)
The position of ownership of the house / residence and building in the Basic Agrarian Law which stipulates that foreigners who can own a house / residence with Right to Use and Right of Lease in Indonesia are foreigners domiciled in Indonesia. The Right to Use shall be matured for the first time in 25 years, renewable fo a maximum period of 20 years, and renewable for a maximum period of 25 years.The lease right are a form of legal relation of lease agreement of existing house / building on a plot of land to be accupied without control over the right to land. Given this rule of home ownership by foreigners can provide legal certainty, increase foreign investment in Indonesia and can provide jobs to reduce unemployment.Keywords: Foreign Citizen, Right to Use, Rental Rights.